Low-Dose Antithymocyte Globulin: A Pragmatic Approach to Treating Stage 2 Type 1 Diabetes - Foster, Timothy P.; Jacobsen, Laura M.; Bruggeman, Brittany; Salmon, Chelsea; Hosford, Jennifer; Chen, Angela; Cintron, Miriam; Mathews, Clayton E.; Wasserfall, Clive; Brusko, Maigan A.; Brusko, Todd M.; Atkinson, Mark A.; et al. (Diabetes care, 2024)
Low-dose antithymocyte globulin (ATG) (2.5 mg/kg) preserves C-peptide and reduces HbA1c in new-onset stage 3 type 1 diabetes, yet efficacy in delaying progression from stage 2 to stage 3 has not been evaluated. Children (n = 6) aged 5-14 years with stage 2 type 1 diabetes received off-label, low-dose ATG. HbA1c, C-peptide, continuous glucose monitoring, insulin requirements, and side effects were followed for 18-48 months. Three subjects (50%) remained diabetes free after 1.5, 3, and 4 years of follow-up, while three developed stage 3 within 1-2 months after therapy. Eighteen months posttreatment, even disease progressors demonstrated near-normal HbA1c (5.1% [32 mmol/mol], 5.6% [38 mmol/mol], and 5.3% [34 mmol/mol]), time in range (93%, 88%, and 98%), low insulin requirements (0.17, 0.18, and 0.34 units/kg/day), and robust C-peptide 90 min after mixed meal (1.3 ng/dL, 2.3 ng/dL, and 1.4 ng/dL). These observations support additional prospective studies evaluating ATG in stage 2 type 1 diabetes.